2017
DOI: 10.1016/j.anr.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Protective Factors of Demoralization among Cancer Patients in Taiwan: An Age-matched and Gender-matched Study

Abstract: Early and appropriate demoralization assessment of cancer patients' demographic and disease characteristics is very important in clinical settings. Healthcare providers might regularly monitor demoralization in cancer patients, and develop related nursing care guidelines or treatment for demoralization in cancer patients. The study results can be a reference for healthcare providers who work with cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
3
17
3
Order By: Relevance
“…Family, friends and partners are among the most often mentioned areas relevant to the meaning of life (Fegg et al, 2008 ). Higher income was associated with lower demoralization which is in accordance with findings describing monthly income as protective factor of demoralization (Lee et al, 2012 ; Li et al, 2017 ). This could be due to existential concerns as a result of financial insecurity.…”
Section: Discussionsupporting
confidence: 89%
“…Family, friends and partners are among the most often mentioned areas relevant to the meaning of life (Fegg et al, 2008 ). Higher income was associated with lower demoralization which is in accordance with findings describing monthly income as protective factor of demoralization (Lee et al, 2012 ; Li et al, 2017 ). This could be due to existential concerns as a result of financial insecurity.…”
Section: Discussionsupporting
confidence: 89%
“…There were 34 cross-sectional studies, 5 longitudinal studies and 1 randomised controlled trial included in this review. Two studies (Li et al, 2016(Li et al, , 2017 included in this review reported different relevant analysis findings based on the same study population.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies identified no demographic factors as being predictive of higher levels of demoralisation, although cohort sizes were smaller for some (see Table 3) with potential sample bias resulting (Arts-de Jong et al, 2018; Bovero et al, 2019; Cersonsky et al, 2019; Quintero Garzón et al, 2018). Other studies reported that patients with lower education (Bailey et al, 2020; Bobevski et al, 2015; Hsu et al, 2021; Ko et al, 2018; Li et al, 2016; Tang et al, 2020; Wu et al, 2018), lower income level (Cheng et al, 2019; Hsu et al, 2021; Li et al, 2016, 2017; Tang et al, 2020), female gender (De Weert et al, 2017; Ignatius and De La Garza, 2019; Ko et al, 2018; Li et al, 2016) and younger age (De Weert et al, 2017; Ignatius and De La Garza, 2019; Koo et al, 2018; Vehling et al, 2015) were relatively more demoralised. Additionally, being single/non-partnered (Ignatius and De La Garza, 2019; Li et al, 2016) and having poor social support were found to mediate higher demoralisation (An et al, 2018; Li et al, 2017; Philipp et al, 2020; Quintero Garzón et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that depressive patients tend to perceive that the source of distress is internal to them and often lack motivation, while in contrast, demoralized patients perceive that the source of distress is external to them and frequently present with uncertainty about the direction their actions should follow, implying that their motivation is intact [1]. Multiple studies have shown that demoralization is more associated with psychological state rather than the physical condition [12][13][14]. Furthermore, for clinicians or medical staff devoted to caring for patients with cancer, patients under hospice care, or patients with chronic psychosis, the most important concern is not only to differentiate demoralized patients from depressive ones, but also to provide appropriate and efficient treatment strategies for patients with a high demoralization level [1].…”
Section: Open Accessmentioning
confidence: 99%